A bio-based phase change thermal conductive material and its preparation method

CN122726643APending Publication Date: 2026-09-11DONGGUAN NYSTEIN ELECTRONICS MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611052813.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-15
Publication Date
2026-09-11

AI Technical Summary

Technical Problem

首先,现有高导热填料的添加虽能一定程度提升导热系数,但填料与有机基体之间的界面相容性较差,导致界面热阻较大,导热性能的提升有限

Benefits of technology

(1)本发明中,聚乳酸末端羧基与铝粉表面的羟基通过化学键合作用实现界面结合,改善了有机无机界面的相容性;硬脂酸通过末端羧基与铝粉表面发生化学结合,形成有机包覆层,利用空间位阻效应防止铝粉团聚,确保填料在基体中的均匀分散。在上述协同作用下,本发明材料的导热系数达7.4~8.2 W/(m·K),界面热阻低至0.04~0.08℃·cm2/W。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122726643A_ABST
    Figure CN122726643A_ABST
Patent Text Reader

Abstract

This invention relates to a bio-based phase change thermal conductive material and its preparation method, belonging to the technical field of phase change energy storage materials. The material comprises soybean wax, castor oil, polylactic acid, stearic acid, and spherical aluminum powder, wherein the spherical aluminum powder is a composite of three particle sizes. It is prepared by mixing and heating the organic components to 145-155°C to melt them, then adding the spherical aluminum powder and kneading for 25-35 minutes. In this invention, soybean wax is used as the phase change material, and polylactic acid acts as an encapsulation framework to adsorb and fix the liquid phase change components to prevent leakage. Its terminal carboxyl groups achieve interfacial bonding with the hydroxyl groups on the aluminum powder surface through chemical bonding. Stearic acid acts as a dispersant to ensure uniform dispersion of the aluminum powder. The material of this invention has a thermal conductivity of 7.4-8.2 W / (m·K) and an interfacial thermal resistance as low as 0.04-0.08 °C·cm. 2 It is leak-free, environmentally friendly, and has a simple process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of phase change energy storage materials technology, and more particularly to a bio-based phase change thermal conductive material and its preparation method. Background Technology

[0002] Phase change thermally conductive materials (PCTs) are high-performance thermal interface materials capable of intelligently adjusting their physical state according to temperature changes. These materials absorb or release a large amount of heat energy during phase change, achieving efficient thermal management. Simultaneously, PCTs combine the high thermal conductivity and low thermal resistance of traditional thermal grease with the ease of use of thermal pads. However, traditional organic PCTs (such as paraffin wax and polyethylene glycol) generally suffer from low thermal conductivity, typically only 0.2~0.3 W / (m·K), preventing heat from quickly penetrating the material for storage or release, thus limiting their response speed and temperature control effectiveness in practical applications. Furthermore, traditional PCTs exhibit limitations during solid-state transitions. Leakage is prone to occur during liquid phase change, which not only degrades material properties but may also contaminate electronic components or equipment, posing a reliability risk.

[0003] To overcome the aforementioned shortcomings, existing technologies typically employ the following methods: First, adding highly thermally conductive fillers, such as metal particles (aluminum powder, copper powder), carbon-based materials (such as carbon nanotubes, graphene), or ceramic materials (boron nitride, alumina), to the phase change material to improve its thermal conductivity. Second, encapsulating and shaping the phase change material using porous carriers (such as porous carbon, polymer frameworks, etc.), utilizing capillary forces or surface tension to adsorb the liquid phase change material into the pores and prevent leakage. Third, fixing phase change segments into a polymer network through chemical cross-linking or grafting methods to prepare a solid phase change material. Solid-state change materials.

[0004] While the aforementioned techniques have improved the performance of traditional phase change materials to some extent, several shortcomings remain. First, although the addition of existing high thermal conductivity fillers can improve thermal conductivity to a certain degree, the poor interfacial compatibility between the filler and the organic matrix results in high interfacial thermal resistance, limiting the improvement in thermal conductivity. Second, commonly used porous supports (such as porous carbon) are mostly petroleum-based materials, which are non-renewable and difficult to degrade, contradicting the trend of green and environmentally friendly development. Third, existing technologies often employ complex processes such as multi-step composites or vacuum impregnation, increasing preparation costs and process difficulty. Finally, the thermal conductivity of existing bio-based phase change materials is generally low, making it difficult to meet the rapid thermal response requirements of high-power electronic devices. Furthermore, traditional phase change materials in solid-state... Leakage is prone to occur during liquid phase change, and existing physical adsorption or physical encapsulation methods are difficult to maintain a stable leak-proof effect during long-term use. Summary of the Invention

[0005] To address the aforementioned problems in the existing technology, this invention provides a bio-based phase change thermal conductive material and its preparation method. This invention uses soybean wax as the phase change material, castor oil to regulate the phase change temperature, polylactic acid as the framework carrier, stearic acid as the dispersant, and utilizes the carboxyl groups at the ends of polylactic acid (…). COOH) and hydroxyl groups on the surface of aluminum powder The chemical bonding between OH groups enables organic compounds to form... The effective combination of inorganic interfaces achieves a synergistic effect of high thermal conductivity, leak-free operation, high reliability, and environmental friendliness. It can be applied to phase change thermal interface materials in fields such as thermal management of electronic equipment, battery thermal control systems, and building energy conservation.

[0006] The objective of this invention can be achieved through the following technical solutions: In a first aspect, a bio-based phase change thermal conductive material is provided, comprising the following raw materials in parts by weight: 1-2 parts soybean wax; 3-5 parts castor oil; 3-4 parts of polylactic acid; 1-2 parts stearic acid; 175-185 parts of spherical aluminum powder; The spherical aluminum powder is a blend of three types of spherical aluminum powder with particle sizes of 3μm, 10μm and 20μm.

[0007] Furthermore, the aforementioned bio-based phase change thermal conductive material comprises the following raw materials in parts by weight: 0.5 parts of soybean wax; 5 parts castor oil; 3 parts polylactic acid; 1.5 parts stearic acid; The mass ratio of spherical aluminum powder with particle sizes of 3μm, 10μm and 20μm is 54:36:90.

[0008] Furthermore, the melting point of the soybean wax is 45~50℃.

[0009] Preferably, the soybean wax has a melting point of 46°C.

[0010] Furthermore, the polylactic acid melt index is 10~25 g / 10 min.

[0011] In this invention, polylactic acid (PLA) serves a dual function: encapsulation framework and interfacial bonding. On one hand, the PLA molecular chains form a cross-linked framework structure within the matrix, binding the liquid soybean wax and castor oil and preventing leakage of the phase change fraction. On the other hand, the carboxyl groups at the ends of the PLA molecular chains (…) COOH) and hydroxyl groups on the surface of aluminum powder OH) achieves interfacial bonding through chemical bonding, improving organic matter Inorganic interface compatibility. This improves thermal conductivity and long-term reliability.

[0012] Furthermore, in the spherical aluminum powder, the mass ratio of spherical aluminum powder with particle sizes of 3μm, 10μm and 20μm is (27~54):(27~54):(90~110).

[0013] Furthermore, the mass ratio of the spherical aluminum powders with particle sizes of 3μm, 10μm and 20μm is 36:54:90, 54:36:90, 53:27:100, 35:35:110 or 27:53:100.

[0014] In a second aspect, a method for preparing a bio-based phase change thermally conductive material as described in the first aspect is provided, comprising the following steps: Soy wax, castor oil, polylactic acid, and stearic acid are mixed, heated to melt, and then spherical aluminum powder is added and kneaded to obtain a bio-based phase change thermal conductive material.

[0015] Stearic acid is an amphiphilic molecule. Its long-chain alkyl group has good compatibility with organic matrices (soybean wax, castor oil), while the terminal carboxyl group (-COOH) forms an organic coating layer on the filler surface by chemically combining with the hydroxyl group (-OH) on the surface of aluminum powder. The steric hindrance effect of its long-chain alkyl group prevents the agglomeration of aluminum powder and ensures its uniform dispersion in the matrix.

[0016] The terminal carboxyl groups of polylactic acid (PLA) achieve interfacial bonding with the hydroxyl groups on the aluminum powder surface through chemical bonding; stearic acid, through its terminal carboxyl groups, chemically bonds with the hydroxyl groups on the aluminum powder surface, forming an organic coating layer on the aluminum powder surface. The synergistic effect of both achieves an organic coating layer. The effective combination of inorganic interfaces, along with the prevention of aluminum powder agglomeration through steric hindrance, further enhances the product's effectiveness.

[0017] Furthermore, the heating temperature is 145~155℃.

[0018] Preferably, the heating temperature is 150°C.

[0019] Furthermore, the kneading time is 25-35 minutes.

[0020] Preferably, the kneading time is 30 minutes.

[0021] Thirdly, the application of the bio-based phase change thermal conductive material as described in the first aspect in the preparation of thermal interface materials for electronic devices, battery thermal management systems, or building energy-saving materials is provided.

[0022] The beneficial effects of this invention are as follows: (1) In this invention, the terminal carboxyl groups of polylactic acid and the hydroxyl groups on the surface of aluminum powder achieve interfacial bonding through chemical bonding, thereby improving the organic... The inorganic interface exhibits compatibility; stearic acid chemically bonds to the aluminum powder surface through its terminal carboxyl groups, forming an organic coating layer. This steric hindrance prevents aluminum powder agglomeration, ensuring uniform dispersion of the filler within the matrix. Under these synergistic effects, the material of this invention achieves a thermal conductivity of 7.4–8.2 W / (m·K) and an interfacial thermal resistance as low as 0.04–0.08 °C·cm. 2 / W.

[0023] (2) In this invention, polylactic acid molecular chains intertwine to form a cross-linked backbone structure in the matrix. This backbone structure binds the liquid soybean wax and castor oil, firmly confining them within the backbone, preventing the liquid phase change components from flowing freely and effectively preventing precipitation and leakage. After reliability testing, the changes in the material's thermal conductivity and interfacial thermal resistance are minimal. In particular, in Example 2, the thermal conductivity remains at 8.0 W / (m·K), and the interfacial thermal resistance only increases from 0.043 to 0.045 °C·cm. 2 / W.

[0024] (3) All raw materials used in this invention are bio-based: soybean wax is derived from soybean oil, castor oil from castor seeds, polylactic acid from renewable resources such as corn starch or sugarcane, and stearic acid can also be derived from vegetable oils. The entire system does not contain petroleum-based components, reducing dependence on fossil fuels and lowering carbon emissions. At the same time, the material has good biodegradability and will not cause persistent pollution to the environment after disposal, meeting the requirements of green environmental protection and sustainable development.

[0025] (4) The present invention only requires one high-temperature kneading to complete the preparation of materials, without the need for complex processes such as multi-step compounding or vacuum impregnation. The preparation process is significantly simplified, which is conducive to reducing production costs and improving production efficiency. Attached Figure Description

[0026] To facilitate understanding by those skilled in the art, the present invention will be further described below with reference to the accompanying drawings.

[0027] Figure 1 Organic components in the bio-based phase change thermal conductive material of this invention Schematic diagram of inorganic interface chemical bonding. Detailed Implementation

[0028] To further illustrate the technical means and effects of the present invention in achieving its intended purpose, the following detailed description of the specific implementation methods, structures, features, and effects of the present invention, in conjunction with the accompanying drawings and preferred embodiments, is provided.

[0029] The raw materials used in the examples are from:

[0030] Example 1 Formula (parts by weight): 1 part soybean wax, 3 parts castor oil, 4 parts polylactic acid, 2 parts stearic acid, 36 parts spherical aluminum powder (3μm), 54 parts spherical aluminum powder (10μm), and 90 parts spherical aluminum powder (20μm).

[0031] Preparation method: One part soybean wax, three parts castor oil, four parts polylactic acid, and two parts stearic acid were added to a kneader and heated to 150°C until the raw materials were in a molten and flowing state. Then, 36 parts of spherical aluminum powder with a particle size of 3 μm, 54 parts of spherical aluminum powder with a particle size of 10 μm, and 90 parts of spherical aluminum powder with a particle size of 20 μm were added, and the mixture was kneaded for 30 minutes to ensure thorough and uniform mixing. Heating was then stopped, and the mixture was cooled to room temperature to obtain the bio-based phase change thermal conductive material.

[0032] Example 2 Formula (parts by weight): 0.5 parts soybean wax, 5 parts castor oil, 3 parts polylactic acid, 1.5 parts stearic acid, 54 parts spherical aluminum powder (3μm), 36 parts spherical aluminum powder (10μm), and 90 parts spherical aluminum powder (20μm).

[0033] Preparation method: Soybean wax, castor oil, polylactic acid, and stearic acid were added to a kneader and heated to 150°C until the raw materials were in a molten and flowing state. Then, spherical aluminum powder with a particle size of 3 μm, 10 μm, and 20 μm were added and kneaded for 30 minutes to ensure thorough and uniform mixing. Heating was then stopped, and the mixture was cooled to room temperature to obtain the bio-based phase change thermal conductive material.

[0034] Example 3 Formula (parts by weight): 2 parts soybean wax, 4 parts castor oil, 3 parts polylactic acid, 1 part stearic acid, 53 parts spherical aluminum powder (3μm), 27 parts spherical aluminum powder (10μm), and 100 parts spherical aluminum powder (20μm).

[0035] Preparation method: Soybean wax, castor oil, polylactic acid, and stearic acid were added to a kneader and heated to 150°C until the raw materials were in a molten and flowing state. Then, spherical aluminum powder with a particle size of 3 μm, 10 μm, and 20 μm were added and kneaded for 30 minutes to ensure thorough and uniform mixing. Heating was then stopped, and the mixture was cooled to room temperature to obtain the bio-based phase change thermal conductive material.

[0036] Example 4 Formula (parts by weight): 1.5 parts soybean wax, 3 parts castor oil, 4 parts polylactic acid, 1.5 parts stearic acid, 35 parts spherical aluminum powder (3μm), 35 parts spherical aluminum powder (10μm), and 110 parts spherical aluminum powder (20μm).

[0037] Preparation method: Soybean wax, castor oil, polylactic acid, and stearic acid were added to a kneader and heated to 150°C until the raw materials were in a molten and flowing state. Then, spherical aluminum powder with a particle size of 3 μm, 10 μm, and 20 μm were added and kneaded for 30 minutes to ensure thorough and uniform mixing. Heating was then stopped, and the mixture was cooled to room temperature to obtain the bio-based phase change thermal conductive material.

[0038] Example 5 Formula (parts by weight): 0.5 parts soybean wax, 4 parts castor oil, 4 parts polylactic acid, 1.5 parts stearic acid, 27 parts spherical aluminum powder (3μm), 53 parts spherical aluminum powder (10μm), and 100 parts spherical aluminum powder (20μm).

[0039] Preparation method: Soybean wax, castor oil, polylactic acid, and stearic acid were added to a kneader and heated to 150°C until the raw materials were in a molten and flowing state. Then, spherical aluminum powder with a particle size of 3 μm, 10 μm, and 20 μm were added and kneaded for 30 minutes to ensure thorough and uniform mixing. Heating was then stopped, and the mixture was cooled to room temperature to obtain the bio-based phase change thermal conductive material.

[0040] Example 6 Formula (parts by weight): 0.5 parts soybean wax, 5 parts castor oil, 3 parts polylactic acid, 1.5 parts stearic acid, 52.5 parts spherical aluminum powder (3μm), 35 parts spherical aluminum powder (10μm), and 87.5 parts spherical aluminum powder (20μm).

[0041] Preparation method: Soybean wax, castor oil, polylactic acid, and stearic acid were added to a kneader and heated to 145°C until the raw materials were in a molten and flowing state. Then, spherical aluminum powder with a particle size of 3 μm, 10 μm, and 20 μm was added and kneaded for 35 minutes to ensure thorough and uniform mixing. Heating was then stopped, and the mixture was cooled to room temperature to obtain the bio-based phase change thermal conductive material.

[0042] Example 7 Formula (parts by weight): 0.5 parts soybean wax, 5 parts castor oil, 3 parts polylactic acid, 1.5 parts stearic acid, 55.5 parts spherical aluminum powder (3μm), 37 parts spherical aluminum powder (10μm), and 92.5 parts spherical aluminum powder (20μm).

[0043] Preparation method: Soybean wax, castor oil, polylactic acid, and stearic acid were added to a kneader and heated to 155°C until the raw materials were in a molten and flowing state. Then, spherical aluminum powder with a particle size of 3 μm, 10 μm, and 20 μm was added, and the mixture was kneaded for 25 minutes to ensure thorough and uniform mixing. Heating was then stopped, and the mixture was cooled to room temperature to obtain the bio-based phase change thermal conductive material.

[0044] Comparative Example 1 Based on Example 2, only spherical aluminum powder of a single particle size (10μm) was used, and everything else was the same as in Example 2.

[0045] Comparative Example 2 Based on Example 2, spherical aluminum powder (3μm) and spherical aluminum powder (20μm) were compounded, and all other aspects were the same as in Example 2.

[0046] Comparative Example 3 Based on Example 2, the mass ratio of spherical aluminum powder with particle sizes of 3μm, 10μm and 20μm was replaced with 10:80:90, and everything else was the same as in Example 2.

[0047] Comparative Example 4 Based on Example 2, the total amount of aluminum powder was changed to 150 parts (45 parts for 3μm, 30 parts for 10μm, and 75 parts for 20μm), and everything else was the same as in Example 2.

[0048] Comparative Example 5 Based on Example 2, the total amount of aluminum powder was changed to 200 parts (60 parts for 3μm, 40 parts for 10μm, and 100 parts for 20μm), and everything else was the same as in Example 2.

[0049] Comparative Example 6 Based on Example 2, polylactic acid was not added, but everything else was the same as in Example 2.

[0050] Comparative Example 7 Based on Example 2, stearic acid was not added, but everything else was the same as in Example 2.

[0051] Comparative Example 8 Based on Example 2, polylactic acid was replaced with polyurethane, and the rest was the same as in Example 2.

[0052] Comparative Example 9 Three-dimensional porous carbon carriers were prepared by replacing polylactic acid with biomass-based porous carbon and using cassava straw as raw material through a one-step carbonization method.

[0053] Based on Example 2, polylactic acid was replaced with the above-mentioned porous carbon support, and the rest was the same as in Example 2.

[0054] Comparative Example 10 Polylactic acid was replaced with petroleum / coal-based porous carbon, and petroleum pitch was used as the carbon source. The porous carbon carrier was prepared by KOH activation and high-temperature carbonization.

[0055] Based on Example 2, polylactic acid was replaced with the above-mentioned porous carbon support, and the rest was the same as in Example 2.

[0056] Comparative Example 11 Based on Example 2, the aluminum powder was replaced with copper powder, and the rest was the same as in Example 2.

[0057] Comparative Example 12 Based on Example 2, aluminum powder was replaced with aluminum oxide, and the rest was the same as in Example 2.

[0058] Comparative Example 13 Based on Example 2, the aluminum powder was replaced with graphene, and the rest was the same as in Example 2.

[0059] Comparative Example 14 Based on Example 2, castor oil was not added, but everything else was the same as in Example 2.

[0060] Comparative Example 15 Based on Example 2, soybean wax was replaced with paraffin wax, and the rest was the same as in Example 2.

[0061] Comparative Example 16 Based on Example 2, the heating temperature was adjusted to 120°C, and the rest was the same as in Example 2.

[0062] Comparative Example 17 Based on Example 2, the kneading time was adjusted to 10 minutes, and the rest was the same as in Example 2.

[0063] Comparative Example 18 Referring to known methods for preparing biomass porous carbon-based composite phase change materials in the field, porous carbon carriers were prepared by high-temperature carbonization of pine wood as raw material, and paraffin was loaded by vacuum melt impregnation method to obtain biomass porous carbon / paraffin composite phase change materials.

[0064] Performance testing I. Testing Methods 1. Thermal conductivity and interfacial thermal resistance Tests were conducted according to ASTM D5470 standard. The material was pressed into flat sheets with a thickness of 0.5–3 mm, and steady-state heat flow tests were performed at 50–80 °C and 0.1–1.0 MPa pressure. For phase change materials, the thermal resistance was measured using the single-thickness method, and the data after subtracting the contact thermal resistance was recorded.

[0065] 2. Reliability testing (thermal cycling durability) After aging the material in an 85℃ / 85%RH constant temperature and humidity chamber for 1000 hours, the thermal conductivity and interfacial thermal resistance were tested again.

[0066] 3. Leakage test After placing the material in an 85℃ constant temperature chamber for 24 hours, observe whether any liquid components are released from the surface.

[0067] Visually inspect the surface for oil droplets or seepage, and press on A4 paper or filter paper to check for oil stains.

[0068] II. Test Results Table 1 Performance test results of Examples 1-7

[0069] Table 2 Performance test results of Comparative Examples 1-18

[0070] The results showed that like Figure 1 As shown, the polylactic acid molecular chain contains carboxyl groups at its ends ( COOH), which reacts with the hydroxyl groups on the surface of the spherical aluminum powder. OH) achieves interfacial bonding through chemical bonding; stearic acid molecules also contain carboxyl groups at their ends ( COOH reacts chemically with the aluminum powder surface, forming an organic coating layer. The synergistic effect of these two processes achieves both organic and chemical bonding. The effective combination of the inorganic interface, along with the steric hindrance preventing aluminum powder agglomeration, improves thermal conductivity and long-term reliability.

[0071] The thermal conductivity of Examples 1-7 is 7.4-8.2 W / (m·K), and the interfacial thermal resistance is as low as 0.04-0.08℃·cm. 2 / W, and none of them leaked. Among them, Example 2 has the best overall performance, with a thermal conductivity of 8.0 W / (m·K), no decay after reliability testing, and only a slight increase in thermal resistance, achieving a balance between high thermal conductivity and high reliability.

[0072] Compared to Example 2, Comparative Example 1 used only aluminum powder of a single particle size, with a thermal conductivity of 4.2 W / (m·K) and an interfacial thermal resistance of 0.22℃·cm. 2 / W. Comparative Example 2 lacked an intermediate particle size (10μm), using only 3μm and 20μm particle sizes, resulting in a thermal conductivity of 5.6 W / (m·K). Comparative Example 3, although using three particle sizes, deviated from the range defined in this invention (only 10 parts of 3μm and as many as 80 parts of 10μm), resulting in a thermal conductivity of 6.2 W / (m·K). Comparative Example 4 had insufficient total aluminum powder, while Comparative Example 5 had excessive aluminum powder, both of which reduced thermal conductivity and reliability. Comparative Example 6, without polylactic acid, experienced leakage, increased interfacial thermal resistance, and decreased thermal conductivity. Comparative Example 7, without stearic acid, had a thermal conductivity of 6.8 W / (m·K), but reliability further decreased to 6.2. Comparative Example 8, replacing polylactic acid with polyurethane, could not form hydrogen bonds with the hydroxyl groups on the aluminum powder surface, resulting in high interfacial thermal resistance and reduced thermal conductivity. Comparative Example 9, where polylactic acid was replaced with biomass-based porous carbon, resulted in leakage. The thermal conductivity was 5.0 W / (m·K), and the interfacial thermal resistance was 0.18℃·cm. 2 / W. Comparative Example 10, where polylactic acid was replaced with petroleum / coal-based porous carbon, showed leakage, a thermal conductivity of 4.5 W / (m·K), and an interfacial thermal resistance of 0.22℃·cm. 2 / W. In Comparative Examples 11, 12, and 13, aluminum powder was successively replaced with copper powder, alumina, and graphene, resulting in high interfacial thermal resistance and decreased thermal conductivity. In Comparative Example 14, without the addition of castor oil, the thermal resistance increased to 0.12℃·cm after reliability testing. 2 / W. Comparative Example 15 replaced soybean wax with paraffin wax, with a thermal conductivity of 6.8 W / (m·K). Comparative Example 16 had a lower heating temperature, a thermal conductivity of 5.2 W / (m·K), and a thermal resistance of 0.18℃·cm. 2 / W. Performance degrades after reliability testing. Comparative Example 17 has a short kneading time and a thermal conductivity of 5.8 W / (m·K), but the thermal conductivity decreases after reliability testing. Comparative Example 18 refers to existing biomass porous carbon / paraffin composite phase change materials, whose thermal conductivity is 0.48~1.2 W / (m·K), and paraffin leakage occurs in porous carbon. In addition, this scheme uses a multi-step carbonization + vacuum impregnation process, which has a long preparation cycle and high energy consumption.

[0073] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A bio-based phase change thermal conductive material, characterized in that, Including the following parts by weight of raw materials: 1-2 parts soybean wax; 3-5 parts castor oil; 3-4 parts of polylactic acid; 1-2 parts stearic acid; 175-185 parts of spherical aluminum powder; The spherical aluminum powder is a blend of three types of spherical aluminum powder with particle sizes of 3μm, 10μm and 20μm.

2. The bio-based phase change thermal conductive material according to claim 1, characterized in that, Including the following parts by weight of raw materials: 0.5 parts of soybean wax; 5 parts castor oil; 3 parts polylactic acid; 1.5 parts stearic acid; The mass ratio of spherical aluminum powder with particle sizes of 3μm, 10μm and 20μm is 54:36:

90.

3. The bio-based phase change thermal conductive material according to claim 1, characterized in that, The melting point of the soybean wax is 45~50℃.

4. The bio-based phase change thermal conductive material according to claim 1, characterized in that, The polylactic acid melt index is 10~25 g / 10 min.

5. The bio-based phase change thermal conductive material according to claim 1, characterized in that, The mass ratio of spherical aluminum powder with particle sizes of 3μm, 10μm and 20μm is (27~54):(27~54):(90~110).

6. The bio-based phase change thermal conductive material according to claim 5, characterized in that, The mass ratio of the spherical aluminum powder with particle sizes of 3μm, 10μm and 20μm is 36:54:90, 54:36:90, 53:27:100, 35:35:110 or 27:53:

100.

7. A method for preparing a bio-based phase change thermally conductive material as described in any one of claims 1 to 6, characterized in that, Includes the following steps: Soy wax, castor oil, polylactic acid, and stearic acid are mixed, heated to melt, and then spherical aluminum powder is added and kneaded to obtain a bio-based phase change thermal conductive material.

8. The method for preparing the bio-based phase change thermally conductive material according to claim 7, characterized in that, The heating temperature is 145~155℃.

9. The method for preparing the bio-based phase change thermally conductive material according to claim 7, characterized in that, The kneading time is 25-35 minutes.

10. The application of the bio-based phase change thermal conductive material according to any one of claims 1 to 6 in the preparation of thermal interface materials for electronic devices, battery thermal management systems, or building energy-saving materials.